High School Students' Science Literacy Profile in the Digital Era: A Diagnostic Study for Contextual Learning Development - Salsabila*, Ainus; Indana, Sifak; Setiawan, Beni; Ariwijaya, Toni; Satriawan, Muhammad (Universitas Syiah Kuala, 2025)
The digital era requires students to master scientific literacy to be able to evaluate information and make evidence-based decisions. However, the level of scientific literacy of students in Indonesia is still relatively low, as shown in the latest PISA assessment. This study aims to diagnose the scientific literacy profile of high school students in Pamekasan Regency, Indonesia, as a basis for developing context-based learning. This study used a survey method combined with diagnostic analysis. Data were collected from 114 grade X students of SMAN 1 Pademawu through a scientific literacy test adapted from the PISA 2025 competency framework and has been validated. The test measures three leading indicators: explaining phenomena scientifically, evaluating scientific investigations, and using scientific evidence for decision-making and action. The test consists of 20 multiple-choice questions presented online. In addition, interviews with students and science teachers were conducted to understand the learning conditions. Data analysis was carried out descriptively and quantitatively. The results showed that students scientific literacy level was generally low, with the highest score explaining scientific phenomena and the lowest score in using scientific information for decision-making. These findings emphasize the need to develop a learning model that integrates technology and contextual approaches to improve students' scientific reasoning abilities. Thus, this diagnostic profile provides an important overview for developing effective and relevant science learning strategies according to global standards in today's digital era